Increasing Cognitive Abilities In Early Childhood Through The Patting Method In T.A Al-Manaar Ngabar Group B2 - Hikma Raftanisyah; Miftahul Khasanah; Imam Rohani; Risma Fahrul Amin (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2022)
This study was structured with the aim of knowing the effectiveness of using the pat method to improve the cognitive abilities of early childhood in T.A Al-Manaar Ngabar for the academic year 2021/2022, totaling 14 students. This research is a Classroom Action Research (CAR) which consists of 2 cycles with each cycle consisting of 4 stages, namely the first stage is plaining (planning), the second stage is acting (implementing). Observing (observation) and the fourth stage is reflecting (reflecting). This research was conducted in the odd semester of the 2021/2022 academic year, which is from November to December. The subjects of this study were early childhood group B consisting of 14 students. The object of research is physical motor skills and the clapping method. Data collection techniques using observation. Research data obtained during action research until the final assessment of the action. The results showed that the results of the initial test after the action in the first cycle of 14 students there were 7 students (51.66%) experienced an increase, while in the second cycle students (81.66%). Thus the use of the pat method in the theme of introducing the pillars of Islam can improve children's cognitive abilities.